2009
DOI: 10.1016/j.biomaterials.2009.07.054
|View full text |Cite|
|
Sign up to set email alerts
|

Hyaluronic acid-based hydrogels as 3D matrices for in vitro evaluation of chemotherapeutic drugs using poorly adherent prostate cancer cells

Abstract: The current investigation aimed to develop a biomimetic, three-dimensional (3D) culture system for poorly adherent bone metastatic prostate cancer cells (C4-2B) for use as an in vitro platform for anti-cancer drug screening. To this end, hyaluronic acid (HA) derivatives carrying complementary aldehyde (HAALD) and hydrazide (HAADH) groups were synthesized and characterized. In situ encapsulation of C4-2B cells was achieved by simple mixing of HAALD and HAADH in the presence of the cells. Unlike two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
184
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 239 publications
(196 citation statements)
references
References 43 publications
11
184
0
1
Order By: Relevance
“…Poly(lactidecoglycolide), poly(lactic acid), poly(vinyl alcohol), poly( -caprolactone) or polyethylene glycol) (e.g. Poly(lactide-coglycolide), poly(lactic acid), poly(vinyl alcohol), poly( -caprolactone) or polyethylene glycol) [77,78,99,[115][116][117][118][119][120][121]. One advantage of scaffold-based strategies is that it is possible to better manage matrix stiffness/compliance, porosity, and biochemical composition.…”
Section: Mimicking the Ecmmentioning
confidence: 99%
“…Poly(lactidecoglycolide), poly(lactic acid), poly(vinyl alcohol), poly( -caprolactone) or polyethylene glycol) (e.g. Poly(lactide-coglycolide), poly(lactic acid), poly(vinyl alcohol), poly( -caprolactone) or polyethylene glycol) [77,78,99,[115][116][117][118][119][120][121]. One advantage of scaffold-based strategies is that it is possible to better manage matrix stiffness/compliance, porosity, and biochemical composition.…”
Section: Mimicking the Ecmmentioning
confidence: 99%
“…17 Most studies have shown that the cell viability in 3D cultures during the first few days (1-5 days) was not significantly different when compared to that in 2D culture. 30,34 In some cases, 3D cultures showed slightly reduced cell viability 29 when the culture time prolonged, and this was related to the structure of spheroids, which may result in the lack of oxygen and nutrients, and the accumulation of waste at the core of the spheroid as they grow larger. 25 The structures of 3D spheroids.…”
mentioning
confidence: 99%
“…Also, some therapeutics can become adsorbed to the scaffolds, which may lead to a reduction of the amount of therapeutics that reach cancer cells and, consequently, disturb the therapeutic outcome. [35] Furthermore, some of the animal-sourced natural ECM extracts used for the production of matrices may contain residual growth factors and other undefined constituents that may affect spheroids formation, as well as cancer cells responsiveness to drugs. [31] Lastly, the analysis of spheroids that grew on artificial matrices can be difficult, as the imaging of the spheroids by optical and fluorescence techniques depends on the scaffold size and transparency.…”
Section: Introduction: Spheroids As 3d Tumor Tissue Culture Modelsmentioning
confidence: 99%